Caught in the act: how corporate scandals hurt employees - Gadgil, Salil; Sockin, Jason (Review of Finance, 2026)
Abstract Corporate scandals cause employee sentiment to fall sharply and persistently, driven by diminished perceptions of firm culture and management. Workers are not compensated for this loss in job satisfaction, as neither base nor variable pay rise. In fact, employees are six percentage points less likely to receive variable pay and those who do see it decline by an average of 10 percent. We also find suggestive evidence that corporate scandals induce voluntary turnover, particularly for longer-tenured workers. Together, our results demonstrate that rank-and-file employees are not insulated from organizational wrongdoing.